Management of cough in patients with idiopathic interstitial lung diseases in primary care. (30th March 2022) - Sanchez-Ramirez, Diana C.; Kosowan, Leanne; Singer, Alex
Importance: Cough is a common symptom in idiopathic interstitial lung diseases (ILDs), there is little information of its management in primary care. The objective of this study was to explore the frequency of cough-related consultations and the medications prescribed to patients with ILDs in primary care. Methods: This retrospective cohort study used electronic medical records (EMR) from Manitoba primary care providers participating in the Manitoba Primary Care Research Network repository (2014–2019). Cough-related consults and the subsequent medications prescribed to patients with ILDs were identified in the EMR. Results: 295 patients with ILDs were identified, 73 (25%) of them had 141 cough-related consultations (mean 1.9, SD 1.3) during the period studied. In 50 (35%) of the consultations, patients were prescribed one or more of the following: inhaled bronchodilators (34%), nasal corticoids (18%), codeine/opiates (18%), antibiotics (14%), inhaled corticoids (14%), proton pump inhibitors (8%), cough preparations (6%), antihistamines (4%), and oral corticoids (2%). 13 (26%) subsequent cough-related consultations were identified within 6 months, mainly among patients who were prescribed cough preparations, nasal corticoids, antihistamines, and antibiotics. Conclusion: One-quarter of patients with ILDs consulted primary care due to cough, and about a third of them received a prescription to address potentially underlying causes of cough. Although further studies are required to explore the effect of the medications prescribed, recurrent cough consultations suggested that cough preparations, nasal corticoids, and antihistamines are among the least effective treatments. More research is needed to understand the causes and optimal treatment of cough in patients with ILDs.